A retrospective survey evaluating the prescribing tendencies of UK veterinary surgeons, relating to the use of anti-inflammatory drugs in canine angiostrongylosis. (2nd May 2021) - Loverance, Amy; Wright, Ian; Dunning, Mark; Elsheikha, Hany
Abstract : Background: In addition to anti-parasitic therapy, appropriate supportive care is vital for the successful treatment of canine angiostrongylosis. Aim: This study sought to determine the prevalence and reasons for the use of corticosteroids and non-steroidal anti-inflammatory drugs (NSAIDs), by veterinarians, as a supportive treatment for canine angiostrongylosis. Specifically, the study investigated the use of anti-inflammatory drugs in the management of inflammation, anaphylaxis and immune-mediated thrombocytopenia, which can develop in some dogs infected by Angiostrongylus vasorum . Methods: These aims were achieved by surveying UK veterinarians from a non-endemic area, Yorkshire, and an endemic area, South East England, for canine angiostrongylosis. Responses were received from independent, corporate-owned and referral practices. Results: Overall, more veterinarians would administer corticosteroids (80%) compared with NSAIDs (40%). Most respondents surveyed stated administration would be case dependent, including the severity of perceived inflammation. Four of six veterinarians who would never administer NSAIDs cited coagulopathies as the reason for their decision-making. While the regional comparison here revealed no significant differences, wider sampling may produce identifiable trends. Conclusion: The survey responses revealed a lack of understanding of if, when, and why, anti-inflammatories should be administered. Imperatively, further research is needed to address this lacuna.